Comparison of the oral microbiome of siblings using next‐generation sequencing: a pilot study. (27th May 2016) - Lee, H‐S; Lee, JH; Kim, S‐O; Song, JS; Kim, BI; Kim, YJ; Lee, J‐H
Abstract : Objective: The purpose of this study was to compare the oral microbiome of siblings with and without dental caries using next‐generation sequencing. Materials and Methods: To investigate the oral microbiome composition, 14 young siblings, seven with caries and seven without, were enrolled from seven sibling‐pair families. Supragingival plaque samples were collected from the cervicobuccal area of posterior teeth. All samples were analyzed by pyrosequencing, based on the 16S rRNA gene hypervariable regions, V1–V4. Results: The organisms identified belonged to 65 genera. Fifty‐two genera were identified in the subjects with caries and 58 in those without; 45 genera were shared by both groups. In the Shannon index, the caries group showed lower bacterial diversity than the caries‐free group and the difference was significant (Wilcoxon signed‐rank test, P  < 0.05). Additionally, similarities between siblings were evident in analyses based on weighted UniFrac distances ( P  < 0.05). Conclusions: In this study, the diversity of the microbiome was reduced in subjects with dental caries, while similarity between siblings seemed to be retained.